Oxygen for the delivery room respiratory support of moderate-to-late preterm infants. An international survey of clinical practice from 21 countries - James X. Sotiropoulos (2022)
Aim: The aim of this study was to determine clinician opinion regarding oxygen management in moderate-late preterm resuscitation. Methods: An anonymous online questionnaire was distributed through email/social messaging platforms to neonatologists in 21 countries (October 2020-March 2021) via REDCap. Results: Of the 695 respondents, 69% had access to oxygen blenders and 90% had pulse oximeters. Respondents from high-income countries were more likely to have oxygen blenders than those from middle-income countries (72% vs. 66%). Most initiated respiratory support with FiO2 0.21 (43%) or 0.3 (36%) but only 45% titrated FiO2 to target SpO2. Most (89%) considered heart rate as a more important indicator of response than SpO2. Almost all (96%) supported the need for well-designed trials to examine oxygenation in moderate-late preterm resuscitation. Conclusion: Most clinicians resuscitated moderate-late preterm infants with lower initial FiO2 but some cannot/will not target SpO2 or titrate FiO2. Most consider heart rate as a more important indicator of infant response than SpO2.Large and robust clinical trials examining oxygen use for moderate-late preterm resuscitation, including long-term neurodevelopmental outcomes, are supported amongst clinicians.